No Evidence Known Viruses Play a Role in the Pathogenesis of Onchocerciasis-Associated Epilepsy. An Explorative Metagenomic Case-Control Study - Michael Roach; Adrian Cantu; Melissa Krizia Vieri; Matthew Cotten; Paul Kellam; My Phan; Lia van der Hoek; Michel Mandro; Floribert Tepage; Germain Mambandu; Gisele Musinya; Anne Laudisoit; et al. (Pathogens, 2021)
Despite the increasing epidemiological evidence that the Onchocerca volvulus parasite is strongly associated with epilepsy in children, hence the name onchocerciasis-associated epilepsy (OAE), the pathophysiological mechanism of OAE remains to be elucidated. In June 2014, children with unprovoked convulsive epilepsy and healthy controls were enrolled in a case control study in Titule, Bas-Uélé Province in the Democratic Republic of the Congo (DRC) to identify risk factors for epilepsy. Using a subset of samples collected from individuals enrolled in this study (16 persons with OAE and 9 controls) plasma, buffy coat, and cerebrospinal fluid (CSF) were subjected to random-primed next-generation sequencing. The resulting sequences were analyzed using sensitive computational methods to identify viral DNA and RNA sequences. Anneloviridae, Flaviviridae, Hepadnaviridae (Hepatitis B virus), Herpesviridae, Papillomaviridae, Polyomaviridae (Human polyomavirus), and Virgaviridae were identified in cases and in controls. Not unexpectedly, a variety of bacteriophages were also detected in all cases and controls. However, none of the identified viral sequences were found enriched in OAE cases, which was our criteria for agents that might play a role in the etiology or pathogenesis of OAE.